Aromatic Hydroxyketones: Preparation & Physical Properties - Martin, Robert (Springer, 2015)
An important resource for the synthesis of intermediates of specialty chemicals, pharmaceuticals and fine chemicals. Aromatic Hydroxyketones from Butanone to Dotriacontanone provides the reader with exhaustive information covering structure, preparation, physicochemical characteristics, as well as a related bibliography. The handbook is presented in dictionary style, with a logical classification of the ketones, making the information easily available for consultation. The book is aimed at those working in research, development and production applications in various industries (chemistry, pharmacy, cosmetics, paints and perfumes).